Local and regional constraints on relative sea‐level changes in southern Isle of Skye, Scotland, since the Last Glacial Maximum - Louise Best; Alexander R. Simms; Martin Brader; Jerry Lloyd; Juliet Sefton; Ian Shennan (Journal of Quaternary Science, 2022)
New relative sea‐level (RSL) data constrain the timing and magnitude of RSL changes in the southern Isle of Skye following the Last Glacial Maximum (LGM). We identify a marine limit at ~ 23 m OD, indicating RSL ~20 m above present c . 15.1 ka. Isolation basin data, supported by terrestrial and marine limiting dates, record an RSL fall to 11.59 m above present by c . 14.2 ka. This RSL fall occurs across the time of global Meltwater Pulse 1A, supporting recent research on the sources of ice melting. Our new data also help to resolve some of the chronological issues within the existing Isle of Skye RSL record and provide details of the sub‐Arctic marine environment associated with the transition into Devensian Lateglacial climate at c . 14.5 k cal a bp , and the timing of changes in response to the Loch Lomond Stadial climate. Glacio‐isostatic adjustment (GIA) model predictions of RSL deviate from the RSL constraints and reflect uncertainties in local and global ice models used within the GIA models. An empirical RSL curve provides a target for future research.